Milk fat globule epidermal growth factor 8 (MFG-E8) on monocytes is a novel biomarker of disease activity in systemic lupus erythematosus. (January 2021) - Ushikubo, Mari; Saito, Shuntaro; Kikuchi, Jun; Takeshita, Masaru; Yoshimoto, Keiko; Yasuoka, Hidekata; Yamaoka, Kunihiro; Seki, Noriyasu; Suzuki, Katsuya; Oshima, Hisaji; Takeuchi, Tsutomu
Background: Milk fat globule epidermal growth factor (MFG-E8) is related secreted protein which links phosphatidylserine on apoptotic cells and integrin αvβ3/5 on phagocytes. To clarify the clinical significance of MFG-E8 in SLE, we analyzed the correlation between expression level of MFG-E8 in circulating phagocytic leukocytes and clinical parameters of patients. Methods: The study was conducted under a multi-center, prospective cohort design. Patients with one or both BILAG A or B, or SLEDAI- 2 K ≥ 4 with clinical symptoms were defined as the active SLE group. Expression of MFG-E8 on monocytes and concentration in serum were measured by FACS and ELISA, respectively. Results: 96 subjects were enrolled. The absolute number and proportion of MFG-E8-positive monocytes to total monocytes were significantly higher in the active SLE group (p < 0.01). Importantly, the proportion was also significantly correlated with SLEDAI-2K, clinical SLEDAI, as well as serum levels of anti-ds-DNA antibody and complement and C1q. In addition, the proportion of MFG-E8-positive monocytes to total monocytes was significantly decreased from baseline in active SLE patients after 6 months' treatment and increased concordantly with disease activity in 6 refractory cases. Further, in receiver operating characteristic curve analysis for discrimination between active and inactive SLE, the AUC of the proportion of MFG-E8 was 0.854, which was equivalent to classical activity markers such as anti-ds DNA antibody (0.776), complement (0.897) and C1q (0.815) Conclusions: The proportion of MFG-E8-positive monocytes to total monocytes in peripheral blood was positively associated with disease activity in SLE and may be a novel biomarker of disease activity.